An experimental study on stainless steel hybrid tubular joints with square braces and circular chord. (October 2020) - Feng, Ran; Wu, Chaoqun; Chen, Zhenming; Roy, Krishanu; Chen, Boshan; Lim, James B.P.
Abstract: This paper presents an experimental investigation of the load-carrying capacities of stainless steel hybrid tubular X-, T- and Y-joints with square braces and circular chord under monotonic loading. In total, 18 tests are reported on hybrid tubular X-, T- and Y-joints, including 9 tests on X-joints, 4 tests on T-joints and the remaining 5 tests on Y-joints. All test specimens were made from austenitic stainless steel of grade AISI 304. The material properties of the test specimens were determined by tensile coupon tests. The failure modes, load-carrying capacities and axial load versus displacement and deformation curves were obtained for all test specimens. The influences of brace width-to-chord diameter ratio ( β ) on the failure modes and load-carrying capacities of tubular joints were considered. For the specimens with small β value, the chord face plastification was more likely to occur and there was no obvious peak load observed in the load-displacement and load-deformation curves. For the specimens with large β value, the chord side wall failure was dominant. The clear peak load was observed in the load-displacement and load-deformation curves. The test strengths are compared with the results predicted by the current design rules in accordance with International Committee for the Development and Study of Tubular Structures (CIDECT) (2001), Eurocode 3 (EC3) (2005), Chinese Code (GB50017) (2017) and Australian/New Zealand Standard (AS/NZS) (2001). Upon comparison, it is found that the joint strengths calculated using AS/NZS (2001) are larger than test strengths by 2% on average. It is shown that the design formulae provided by CIDECT (2001), EC3 (2005) and GB50017 (2017) are conservative by around 6%, 19% and 20%, respectively, when compared to the test strengths. Highlights: Tests were conducted on stainless steel SHS-to-CHS hybrid tubular T-, Y- and X-joints. The main failure modes were chord face plastification and chord side wall failure. Initial stiffness and joint strengths increased with the increment of the β value. CIDECT is a little conservative, and EC3 and GB50017 are very conservative. AS/NZS is generally appropriate for stainless steel SHS-to-CHS hybrid tubular joints.